Effect of the 75ferrosilicon on the laser cladding on gray cast iron. (May 2019) - Wang, Zhongqi; Zhang, Jianlong; Zhang, Peng; Zhou, Hong; Zhou, Ti
Highlights: 75ferrosilicon as a inoculation is introduced into the laser cladding. Carbon ratio, phase transform and micro-hardness varies with 75ferrosilicon. Grain size is the smallest at 0. 9 wt% 75ferrosilicon. 0.9 wt% 75ferrosilicon is the best proportion for the corrosion resistance. Abstract: The study described a new method which innovatively added 75ferrosilicon as a kind of inoculation into gray cast iron powder before the laser cladding process of gray cast iron. In order to investigate the effect of 75ferrosilicon on the microstructure and properties, we divided the content ratio of 75ferrosilicon into eight groups and compared the variety with the 75ferrosilicon. The result indicates that 75ferrosilicon has a significant impact on grain size, carbon distribution, phase transformation, carbide content, micro-hardness as well as corrosion resistance of cladding zone. 0.9 wt% 75ferrosilicon was proven to be the most suitable addition that not only mostly enhanced the anti-corrosion, minimized the grain size, but also decreased the volume of carbides from 38.74% to 34.07% compared with the 0 wt% 75ferrosilicon.